Esfera pública, serviço social e neoliberalismo: comunicação sem déficit materialista - Pacheco, Alessandra Genú (2020)
The aim of our theses is to demonstrate the emancipatory potential of public sphere category to Social Work, based on Jürgen Habermas’ social theory. This research was motivated, in the first place, by the recognition of new neoliberalist configurations that achieve both public and social spheres, that conducts to the advance of social conservatism. In the second place, the observation of risks on increasing fragility of Social Work’s ethic and politic projects, as a result of diminishing social politics based on which social workers develop their professional activities and also the diminishing of democratic categories, both factors related to neoliberalism. This thesis is based on the presupposition that an imprecise definition of public sphere category motivates other difficulties derived from the identification of possible limits and possibilities in all aspects of the public sphere. Therefore, our thesis is based on the Frankfurt School’s critical theory, mainly derived from Jürgen Habermas’ analysis of the public sphere. Our methodological approach has been structured as it follows: (1) the significance of Frankfurt School’s critical theory approach is an important component of a greater field, namely the critic social theory; and Habermas one of its main second generation contributors; (2) a panoramic approach of Social Work principles, that shapes the basis for debate with Habermas’ public sphere category; (3) the convergence of main criticism of public sphere category in the Brazilian context, considering the recent analysis derived from Wendy Brown, Pierre Dardot e Christian Laval, that allowed some reflection on the emantipatory potential of the public sphere cathegory applied to Social Work. Lastly, the results obtained from this theoretical approach indicates the materialistic déficit of Habermas’ analysis of the public sphere, which could probably be enhanced by the communicative activities that interconnects subaltern public spheres